Back Cover: Advanced Engineering Materials 9∕2013. Issue 9 (3rd September 2013) - Unknown
<x xml:space="preserve">Abstract</x> Investigations in the last years have shown that ultrasonic metal welding is not only a suitable method to join metals. It is also appropriated to realize high strength joints between different material groups like metals to glass, to ceramics or to CFRP as described in the article of G. Wagner et al. on page 792. Recent microstructural analyses demonstrate that a direct contact between the metal surface and the carbon fibers is realized by this pressure welding method. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>